2020
DOI: 10.1111/imj.15129
|View full text |Cite
|
Sign up to set email alerts
|

Trends in practice: attitudes and challenges in the diagnosis, treatment and management of HIV infection in Australia

Abstract: As life expectancy for people living with human immunodeficiency virus (HIV) (PLWHIV) increases, management models for HIV infection are changing. To understand approaches to practice within this shifting climate and across different medical settings, in 2017 we conducted a baseline survey among the main medical practitioner groups responsible for HIV‐infection care in Australia: hospital‐based physicians (HBP), sexual health physicians (SHP) and ‘accredited general practitioners’ (referred to in 2017 study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…With a similar efficacy and safety profile as DTG-based 3DR [ 40 , 41 ], it could be surmised that B/F/TAF was less likely to be discontinued due in part to its novelty. Indeed, a survey of Australian medical practitioners revealed that DTG/ABC/3TC and B/F/TAF were the preferred regimens for ART initiation due to their high barrier to resistance, and over two-thirds selected B/F/TAF as the anticipated preferred regimen for PLW eventually switching ART in the next 3 to 6 months [ 42 ]. The advantages of a single-tablet regimen for adherence and simplification also cannot be ignored [ 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a similar efficacy and safety profile as DTG-based 3DR [ 40 , 41 ], it could be surmised that B/F/TAF was less likely to be discontinued due in part to its novelty. Indeed, a survey of Australian medical practitioners revealed that DTG/ABC/3TC and B/F/TAF were the preferred regimens for ART initiation due to their high barrier to resistance, and over two-thirds selected B/F/TAF as the anticipated preferred regimen for PLW eventually switching ART in the next 3 to 6 months [ 42 ]. The advantages of a single-tablet regimen for adherence and simplification also cannot be ignored [ 35 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, for s100 GPs working in private practice in community, an array of health system barriers impacts their management of HIV including limited access to resources, constraints imposed by short clinical consultation times, poor levels of remuneration and low caseloads that undermine the maintenance of professional expertise (Newman et al., 2015; Smith et al., 2018). Addressing the broad and often complex needs of many PLHIV requires more resources and time than private practitioners working in primary care can afford (Newman et al., 2015; Smith et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bictegravir was the latest oral ARV recommended for initial therapy during the study period, and a tendency to use newer treatment options has been observed over the years in the OPERA cohort. This was captured in a survey targeting Australian medical practitioners where a majority reported that B/F/TAF would be the preferred regimen to switch to in the next 3–6 months [41].…”
Section: Discussionmentioning
confidence: 99%